2019
DOI: 10.1002/essoar.10500389.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seasonal Modulation of Deep Slow-slip and Earthquakes on the Main Himalayan Thrust

Abstract: The interaction between seasonally-induced non-tectonic and tectonic deformation along the Himalayan plate boundary remains debated. Here, we propose that tectonic deformation along this plate boundary can be significantly influenced by the deformation induced by the non-tectonic hydrological loading cycles. We explore seasonal mass oscillations by continental water storage in Southeast Asia and Himalayan arc region using continuous Global Positioning System measurements and satellite data from the Gravity Rec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…The seasonal variation is relatively more in vertical as compared to horizontal displacement components . Panda et al (2018c), have mentioned that the continuous GPS measurements in the Uttarakhand and Nepal Himalaya show relatively higher transient displacement above the base of the seismogenic zone which is the response of modulation in aseismic slip rate on the deep megathrust controlled by the seasonal hydrological load. It is observed that shear-stress perturbations induced by the seasonal hydrological load are about three times larger on the mid-crustal ramp than on the up-dip flat segment of MHT.…”
Section: Non-tectonic Deformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seasonal variation is relatively more in vertical as compared to horizontal displacement components . Panda et al (2018c), have mentioned that the continuous GPS measurements in the Uttarakhand and Nepal Himalaya show relatively higher transient displacement above the base of the seismogenic zone which is the response of modulation in aseismic slip rate on the deep megathrust controlled by the seasonal hydrological load. It is observed that shear-stress perturbations induced by the seasonal hydrological load are about three times larger on the mid-crustal ramp than on the up-dip flat segment of MHT.…”
Section: Non-tectonic Deformationsmentioning
confidence: 99%
“…The thrusts tectonically dividing five litho-tectonic zones of the Himalaya, i.e., Trans-Himalaya, Tethyan Himalaya, Higher Himalaya, Lesser Himalaya, and the Sub-Himalaya, are the Main Central Thrust (MCT), Main Boundary Thrust (MBT) and the Main Frontal Thrust (MFT) in Nepal or Himalayan Frontal Thrust (HFT) in India. These tectonic structures merge into a lowangle crustal decollement thrust sheet called the Main Detachment Fault (MDF) (Panda et al, 2018c;Sreejith et al, 2018), which later modified to Main Himalayan Thrust (MHT) based on observations from the INDEPTH project seismic reflection profiles. The MFT (also known as Himalayan Frontal Thrust or HFT) is a physiographic and tectonic boundary between the Ganga-Brahmaputra alluvial plains and the Tertiary Siwaliks of the Sub-Himalaya .…”
Section: Introductionmentioning
confidence: 99%
“…The anomalous transients reported by Panda et al 1 are observed at some of the GNSS sites that are located above the base of the seismogenic fault, i.e., the Main Himalayan Thrust (MHT). There is evidence that a mid-crustal ramp close to the base of the seismogenic MHT may only exist on some Himalayan sections 5,6 .…”
mentioning
confidence: 98%
“…anda et al 1 analysed 41 continuous Global Navigation Satellite System (GNSS) sites from the Nepal and Garhwal-Kumaun region of the Himalayan arc and found that a few sites, which are located northward about 100 ± 20 km from the Main Frontal Thrust, show higher-amplitude seasonal transients in the horizontal component (predominantly in the north) of the GNSS coordinate time series. They ascribed these transients to changes in aseismic slip rate on the deep megathrust that may be controlled by seasonal hydrological loading 1 . They further invoked that modulation of aseismic slip on the megathrust down-dip of the seismogenic zone is due to the fault resonance process, induced by the seasonal hydrological stress changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation